Mapping optogenetically-driven single-vessel fMRI with concurrent neuronal calcium recordings in the rat hippocampus - Xuming Chen (Nature Portfolio, 2019)
Detailed characterization of large-scale hemodynamic responses linked to specific neural activity remains to be elucidated at the single-vessel level across the subcentimeter scale hippocampal vasculature in vivo. Here, authors use a novel multi-modal fMRI platform to characterize distinct spatiotemporal patterns of hippocampal hemodynamic responses that were correlated to the optogenetically evoked Ca2+ events and to further demonstrate the significantly reduced neurovascular coupling efficiency upon spreading depression-like Ca2+ events.